Accelerating Decreases in the Incidences of Hepatocellular Carcinoma at a Younger Age in Shanghai Are Associated With Hepatitis B Virus Vaccination - Yu, Shunzhang; Zhu, Qirong; Zheng, Ying; Wu, Chunxiao; Ren, Hong; Liu, Xing; Liu, Zhenqiu; Li, Yanting; Pan, Qichao; Zheng, Ying-Jie (Frontiers in Oncology, 2022)
Background: Routine vaccination of infants for protecting against hepatitis B virus (HBV) infection and its serious consequences, including hepatocellular cancer (HCC), has been carried out in Shanghai, China since 1986. We therefore have examined the trend of HBV infection and HCC incidences before and after HBV vaccination over decades to assess the potential influences of the Shanghai HBV vaccination program. Methods: Data on incidences of HBV infection and HCC were collected from the Shanghai Cancer Registry and the Shanghai HBV vaccination follow-up study. Joint-point regression and the Bayesian age-period-cohort statistical analysis methods were used. Results: The incidences of HBV infection dramatically declined from 23.09 and 1.13 per 100,000 for males and females in 2000 to 3.24 (-85.97%) and 0.22 (-80.53%) per 100,000 in 2014, respectively. Sero-epidemiological data from the sampling surveys during 20 years of follow-up showed that less than 1% of people undergoing HBV vaccination have a positive serum HBsAg. Consistently, the annual adjusted standardization rates (ASR) of HCC steadily fell from 33.38 and 11.65 per 100,000 for males and females in 1973 to 17.34 (-49.2%) and 5.60 (-51.9%) per 100,000 in 2014, respectively. The annual percentage change in overall HCC incidences is about -2%. HCC incidences in males at younger age groups (age <50 years old), particularly in those with an age < 34 groups, showed an accelerating decrease over time, whereas HCC incidences significantly declined in female population across all age groups except for those under 19 years old. The results supported that the universal HBV vaccination in newborns is easy to implement with high coverages and is effective for preventing both HBV infection and HCC in populations.